Upregulation of PI3K/AKT/mTOR, FABP5 and PPARβ/δ in human psoriasis and imiquimodinduced murine psoriasiform dermatitis model - Christopher-Chamcheu, Jean; Siddiqui, Imtiaz; Mukhtar, Hasan; Chaves-Rodríguez, María Inés (Acta Dermato-Venereologica, 2016)
Psoriasis is a common, and currently incurable chronic immune-mediated skin disease, with incompletely understood etiology partially due to the unavailability of animal models that can emulate major features of the disease.
Artículo científico
Keywords: Farmacología; Animales; Enfermedades; Ratones; Metabolismo; Research Subject Categories::MEDICINE::Dermatology and venerology,clinical genetics, internal medicine::Dermatology and venerology